ANALISIS PENGARUH INPUT PRODUKSI TERHADAP HASIL USAHATANI JAGUNG DENGAN MODEL (COBB-DOUGLAS) DAN PENDAPATAN DI DESA TADUI KECAMATAN MAMUJU - Halimah Tussadia; Ambo Abd. Kadir Pakanyamong; Wahyu Prianto; Vera Yanti Rappa; Kaharuddin (Jurnal Ilmiah Mahasiswa Fakultas Pertanian, 2026)
Corn production is a strategic commodity in the agricultural sector that plays an important role in food security and increasing farmers' income. Corn production levels are influenced by various factors, including land area and seed use. This study aims to analyze the effect of production inputs on production results and income of corn farming in Tadui Village, Mamuju District using the Cobb-Douglas production function model. The study was conducted in 2025 with a sample of 80 corn farmers through a survey method, using primary and secondary data that were analyzed quantitatively with multiple linear regression in the form of natural logarithms. The results showed that simultaneously the variables of land area, seeds, farming experience, labor, fertilizer, and pesticides significantly affected corn production, while partially only land area and seeds had a significant and positive effect on production, while other variables had no significant effect. Income analysis shows that the average income of corn farmers is IDR 57,925,545 per 0.93 ha per planting season, equivalent to IDR 62,285,532 per hectare. Therefore, it can be concluded that corn farming in Tadui Village, Mamuju District, remains profitable. However, increasing the efficiency of production input use is still needed to increase yields and farmer welfare.